Digital Marketing and Entrepreneurial Marketing in Optimizing Customer Loyalty - Rina Susanti; Lidya Rizki Ananda; Engla Desnim Silvia (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Research objective – The purpose of this study is to determine the effect of digital marketing and entrepreneurial marketing on customer loyalty at Rumah Bintang Embroidery and Embroidery through satisfaction as a mediator. Design/Methodology/Approach – The population is Bukittinggi people aged 25-60 who have shopped at Rumah Bintang Embroidery and Embroidery. A sample of 100 customers was taken through a sampling technique, namely accidental sampling. Findings – Digital marketing variables directly have a positive and significant (significant) effect on customer satisfaction, entrepreneurial marketing variables have a positive and significant (significant) effect on customer satisfaction, digital marketing has a positive and significant (significant) effect on customer loyalty, entrepreneurial marketing has a positive and significant impact significant (significant) on customer loyalty, and job satisfaction has a positive and significant (significant) effect on customer loyalty. Indirectly, digital marketing variables affect customer loyalty variables mediated by customer satisfaction and entrepreneurial marketing variables affect customer loyalty variables mediated by customer satisfaction. Research limitations – This research is limited to customer loyalty variables and research data is taken from 1 Embroidery and Embroidery SMEs in Bukittinggi City. Thus, the results of the study cannot be concluded in general terms. Originality – The focus of the research lies on the relationship between the influence of digital marketing and entrepreneurial marketing on customer loyalty and looks at the mediating role of customer satisfaction variables